Acid whey valorization: novel approaches for probiotic and functional products development - Mutaliyeva, B.; Turkeyeva, E.; Madybekova, G.; Živković, L.; Talluri, VSSL Prasad; Issayeva, A.; Vinceković, M. (Frontiers in Nutrition, 2025)
Acid whey, a byproduct of dairy processing, particularly from Greek yogurt and cottage cheese production, presents significant environmental and economic challenges due to its high organic load and disposal restrictions. However, the unique composition of acid whey, containing proteins, lactose, minerals, and bioactive compounds, presents promising opportunities for the development of functional, value-added products. This review explores innovative approaches to acid whey valorization, emphasizing biotechnological methods, fermentation techniques, and advanced membrane filtration processes. Comparative analysis of sweet and acid whey compositions underscores specific challenges and advantages in acid whey utilization, various valorization strategies, such as membrane filtration and ultrafiltration, osmosis, enzymatic, and microbial processing, highlighting their effectiveness in ingredient recovery and product development. It also identifies suitable microorganisms capable of efficiently metabolizing acid whey and enhancing the nutritional and functional profiles of derived products. Special attention is given to fermented beverages and other functional products developed from acid whey, incorporating novel strategies to optimize fermentation processes. Moreover, this review details recent advancements in probiotic microencapsulation technologies, demonstrating their effectiveness in maintaining and enhancing probiotic viability in acid whey-based functional beverages. The success of these functional products significantly depends on selecting appropriate probiotic strains, encapsulation materials, and innovative microencapsulation methods. Finally, the article addresses current limitations and outlines future research perspectives, highlighting the potential applications of acid whey-derived products in food, beverages, animal feed, and bioenergy sectors.